Blood glucose screening among elderly Malaysians: Who to target? - Cheah, Yong Kang; Goh, Kim-Leng (Ruijin Hospital, Shanghai Jiaotong University School of Medicine and John Wiley & Sons Australia, Ltd, 2016)
Background: Early detection of raised blood glucose can reduce the risk of developing diabetes. Despite being a high-risk group, a significant proportion of the elderly population does not undergo blood glucose screening. The aim of the present study was to examine the factors affecting blood glucose screening among the elderly.Methods: Data from a sample of 2463 respondents in the National Health and Morbidity Survey 2011 were used. Pearson Chi-squared tests were conducted to find factors associated with screening behavior.A logit model was used to analyze the likelihood of screening. Results: Income, age, education, ethnicity, employment status, availability of medical coverage, and smoking behavior were significantly associated with blood glucose screening. The likelihood of blood glucose screening was positively correlated with available monthly income and was higher in those aged 60–69 years, those attaining higher education, Malays, and elderly who are medically covered.Conclusions: The findings of the present study provide insights for health policy formulation for the elderly. As part of their efforts to reduce national health costs, governments should pay particular attention to the elderly, who are likely to be unscreened for blood glucose levels, because they face even larger risk exposure.